One new Mexican Salacia with pedunculate inflorescences (Celastraceae, Salacioideae) - Lombardi, Julio Antonio (Phytotaxa, 2019)
One new species of Salacia (Celastraceae, Salacioideae) with pedunculate inflorescences from Puebla, Mexico, is described: S. pueblana Lombardi. It is distinguished by its flat, canaliculate disc, papillose sepals, and flowers that dry yellowish-green. It resembles S. multiflora (Lam.) DC. subsp. multiflora by its slender branched inflorescence, but differs from it by its flower outline, disc, and sepals.